Bench Mark Survey Report on Bhadrak Block, Government of India - Planning Commission (Planning Commission, 1956)
Among the objectives of evaluation work undertaken by the programme Evaluation Organisation, two of the more important are—(I) assessment of the extent of adoption of improved practices advocated by the community development and national extension programmes and (ii) obtaining insight into the impact of these programmes upon the economic and social life of the rural people. the field officers of the organisation had been making observations on these two aspects in their periodic reports from the time they were posted in the field in May 1953. However, considering the importance of detailed and precise information on these aspects for a proper assessment of the impact of development programmes it was felt that a series of special surveys, should be undertaken in all the evaluation centres for this purpose. Through this initial survey called the Bench Mark Survey (B. M. S.) the position regarding acceptance of sponsored practices and certain aspects of the rural economy related to the development programme would be ascertained as at the time of the survey or for a given period immediately before it. From this base or ‘benchmark’ position, the changes occurring in the area during the course of operation of the projects would be measured by means of repeat surveys undertaken at specified intervals. As the central objective of this survey was to assess the impact of the community development and national extension service programmes upon the economic conditions in the project areas, it was considered necessary to relate the enquiry in a pointed manner to agricultural practices and other features of village life to which these programmes are most directly related.
Bench Mark Survey Report on Bhadrak Block
Government of India